2018
DOI: 10.1007/s00167-018-5030-3
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C demand is increased after total knee arthroplasty: a double-blind placebo-controlled-randomized study

Abstract: The study was registered at the ISRCTN registry with study ID ISRCTN40250576.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 31 publications
1
19
0
1
Order By: Relevance
“…One study (Hasselholt et al, 2015: 1539–1549) has argued that a possible explanation for the findings in this study are that vitamin C stores in the body, particularly those in the adrenal glands, are released during times of stress such as postoperative inflammation. These stores are limited and their depletion a few days postoperatively could explain the decreased levels at postoperative day 4 and postoperative day 7 shown in the study conducted by Behrend et al (2019). This may serve as an explanation as to why vitamin C levels measured in our study did not significantly change from the preoperative day to the postoperative day 2 blood draws.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…One study (Hasselholt et al, 2015: 1539–1549) has argued that a possible explanation for the findings in this study are that vitamin C stores in the body, particularly those in the adrenal glands, are released during times of stress such as postoperative inflammation. These stores are limited and their depletion a few days postoperatively could explain the decreased levels at postoperative day 4 and postoperative day 7 shown in the study conducted by Behrend et al (2019). This may serve as an explanation as to why vitamin C levels measured in our study did not significantly change from the preoperative day to the postoperative day 2 blood draws.…”
Section: Discussionsupporting
confidence: 45%
“…The vitamin C data in this study differed from a study by Behrend et al (2019), which compared range of motion and incidence of arthrofibrosis after TKA in patients receiving 1000 mg of oral vitamin C daily for 50 days perioperatively versus placebo. The investigators (Behrend et al, 2019) measured vitamin C levels on postoperative days 4 and 7, which showed significantly reduced vitamin C levels in the placebo group. The data in our study showed that vitamin C levels did not significantly change during the two-day study period.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…12,58 Recent studies have examined the role of vitamin C supplementation to potentiate patient outcomes following ACL reconstruction and total knee arthroplasty (TKA). 7,[59][60][61][62] Barker et al 62 sought to determine the effect of preoperative vitamin C supplementation on inflammation following ACL reconstruction. A total of oxidant group, receiving 500 mg vitamin C and 200 IU of vitamin E twice daily, or the matching placebo.…”
Section: Acl Reconstruction and Knee Arthroplastymentioning
confidence: 99%
“…62 Barker et al 62 patients undergoing TKA were divided into a placebo group, which received a daily placebo pill, and a vitamin C group, which received 100 mg of oral vitamin C daily. 7 In both groups, the supplementation started on the day before the procedure and lasted for 50 days. The authors found that vitamin C serum concentration decreased following TKA in the placebo group, but not in the vitamin C group, and that patients that experienced drops greater than 30 μmol/L were more likely to develop AF at 1 year.…”
Section: Acl Reconstruction and Knee Arthroplastymentioning
confidence: 99%